Reliability of electronic recording of waiting times in the emergency department. (October 2015) - Gorlicki, Judith; Raynal, Pierre-Alexis; Leleu, Agathe; Riou, Bruno; Ray, Patrick; Freund, Yonathan
<x xml:space="preserve">Abstract</x> We aimed to evaluate the reliability of waiting times (WT) measures electronically retrieved. We prospectively collected true WT in four emergency departments during 20 predefined 2-h inclusion periods, and compared them with the electronically retrieved waiting time (ERWT). We assessed agreement with calculation of rate of outliers (difference exceeding 20 min), bias, and its 95% limits of agreements, and associated Bland and Altman plot. We analyzed 274 patients. The mean difference was −2 min (SD 13) between ERWT and true WT, with a 95% limits of agreements (−28 to 24 min). Bland and Altman plot showed a good agreement, and we report 7% of outliers. Using ERWT, 14 patients (5%) were misclassified as having their target WT exceeded or not. ERWT agree well with the true WT, although the significant rate of outlier and misclassification calls for caution in their interpretation.